Perancangan Sistem Pencatatan Akuntansi Berbasis Microsoft Access Pada Ukm Di Kota Batam - Budi Chandra; Rico Rivaldo (ConCEPt - Conference on Community Engagement Project, 2021)
Devotion to society is carried out in order to provide support to SMEs that have common problems in their operation, namely the Primadona Shop located in Batam City. The obstacle that occurs is that the Primadona Shop has been operating for 18 years, but so far, the recording is still using the manual method, so it is less efficient and effective because it does not have accurate financial reports. The method of collecting data in this study uses methods such as field observations, interviews and documentation. In this practical work, the recording system uses Microsoft Access software. This system is able to produce several functions to record purchases, sales, cash receipts and cash disbursements. In addition, this system can generate reports in the form of sales reports, purchase reports, inventory reports, income statements and balance reports. The system designed is expected to help Primadona Stores in more accurate and effective accounting records to record and report transactions in accordance with applicable accounting standards and regulations and can assist the person in charge of the company in making decisions so that the company can develop in the future.